Gender perspectives on zoonotic disease epidemiology; A strength weakness opportunities threats analysis in Bundibugyo district, Uganda - Clovice Kankya; James Muleme; Lydia Nabawanuka Namakula; George Seruwagi; Christine Mbabazi Mpyangu; Lesley Rose Ninsiima (PLoS ONE, 2025)
Background Gender mainstreaming in zoonotic disease prevention and control is paramount to produce sustainable solutions as well as keeping communities at the human-animal-environment interface safe and healthy. It is important to note that zoonoses register high mortality rates globally once they occur and they are highly transmissible. Hence this study aimed to explore the gender perspectives on zoonotic disease epidemiology using a (strength, weakness, opportunities and threats) SWOT analysis in Bundibugyo district, Uganda. Methods This study employed a descriptive participatory approach, utilizing data gathered sequentially from 12 Key informant interviews, 4 In-depth interviews and 4 Focus group discussions methods in Bundibugyo district. Interviews used interdisciplinary groups systematically using a SWOT analysis. The research methodology employed an interpretative phenomenological analysis (IPA) approach allowing participants to articulate their perspectives in their own words. Data analysis was done using both inductive and deductive thematically using NVIVO 12 pro, facilitating the development of codes, sub-themes, and themes. Results The results of this study prioritized key zoonotic diseases within the district that affect community health. The key themes from these results a) Threats increasing risk of zoonotic spillover, b) Community weaknesses increasing zoonotic diseases occurrence, c) Community strength for zoonotic disease management, prevention and control, d) Opportunities for communities in management of zoonotic diseases. The study emphasizes that political instability, land migration, food insecurity, cultural hunting practices, and climate change act to increase the risk of zoonotic diseases. Complications arise from the mis-identification of diseases due to similar symptoms, and a lack of community education about these diseases. The risk of exposure is influenced by gender roles, with men, who generally interact more with animals, at higher risk. Conversely, women, due to their roles in caring for the sick and involvement in child immunization, are at risk but also play a crucial role in disease control. Despite these challenges, there are opportunities for disease management and prevention such as leveraging experienced health workers for disease identification and education, utilizing local communication channels, engaging opinion leaders for effective risk communication, and providing regular training for health workers could address these issues. However, limited funding hinders the execution of recommended strategies such as regular surveillance, tracing of suspected cases, and health register reviews. Conclusion This study emphasizes the necessity of gender-sensitive approaches in understanding and mitigating zoonotic diseases, advocating for strategies that recognize socio-cultural factors, promote health education, and tailor interventions to provide comprehensive care and protection for all, irrespective of gender.